A PARTICIPAÇÃO PÚBLICA EM CONSELHOS DE SAÚDE FRENTE À DICOTOMIA LEIGOS E PERITOS - Joel Paese (Universidade Federal do Maranhão, 2010)
The aim of this paper is to discuss the participation of the civil society in social policies councils, focusing their actions on health councils .In arder to achieve this aim we will analyze the problem of governance and empowerment in arder to capture two simultaneous movements: the first one relates to decision making in the context of the relationship between lay knowledge and expert advice on health councils, and the second one deals with the participation of the laity in decision-making in management councils. It is concluded that research considering the relationship between lay people and experts in decision making in health advice may be a useful tool for analyzing the possibilities of achieving democracy, considering the importance not to block public participation when health process decision should not be based only upon expertise.